A racionális viselkedés elmélete (Szociológiai Szemle, 2024)
János Harsányi, the 1994 Nobel laureate in economics was born and lived in Hungary until 1948, when he fled from the country amidst adventurous conditions. Prior to his escape he worked as a social scientist together with László Cseh-Szombathy and Géza Perjés in Sándor Szalay’s institute.In spring this year he came to Hungary and held a lecture for the interested public. In this paper he summaries the more important findings of the theories of games, bargaining and usefulness and his achievements accomplished in these fields of science for those who are not familiar with his field of research.